Measurement of fat digestion in early life using a stable isotope breath test. Issue 3 (September 1993) - McClean, P; Harding, M; Coward, W A; Green, M R; Weaver, L T
Abstract : 13C breath tests are a safe, non-invasive way of assessing nutrient digestion and absorption that can be used repeatedly in infancy and childhood. The aim of this study was to assess their value for measuring fat digestion in infants and young children with cystic fibrosis, and healthy controls whose pancreatic exocrine function is immature, and to monitor pancreatic enzyme supplementation. Six infants with cystic fibrosis (aged 10-18 months) and nine healthy controls (aged 6-19 months) were studied. After an overnight fast each child ingested 7.5 mg/kg 13C trioctanoin (99 atom % excess) followed by a known volume of milk. Breath samples were collected before and at 30 minute intervals thereafter for five hours. The 13C enrichment of expired carbon dioxide was measured by gas isotope ratio mass spectrometry. The mean (SD) percentage dose recovery of 13C was 13.5 (5.3) for the cystic fibrosis group and 24.2 (6.7) for the healthy controls. When those with cystic fibrosis were studied after supplementary pancreatic enzymes, the mean percentage dose recovery rose to 17.1 (6.9). Total intraluminal lipolysis was diminished by 44% in young children with cystic fibrosis. Pancreatic enzyme supplements improved digestion by 27%. The 13C trioctanoin breath test was effective in detecting fat maldigestion and can be used to measure the benefits of enzyme supplements in early life.